Transport emissions and electric mobility in private transport in the Republic of Slovenia - Muhič, Simon; Čikić, Ante; Pištan, Jadran; Stojkov, Marinko; Bošnjaković, Mladen (2018)
Since the ratification of the Kyoto Protocol more and more emphasis is laid on reducing greenhouse gas emissions. The article analyses the feasibility of introducing electric vehicles into traffic rather than vehicles with internal combustion engines. From standpoint of emission sources use of electricity for transport is analysed with stress on private cars and typical emissions from power sector by energy conversion in Slovenia. Results of research shows that electric car has a little more than twice better efficiency of the primary energy use, taking into account only efficiency in the energy chain. Electric mobility brings a more efficient use of energy in road transport with demand to reduce emission at power generation. So presented number can vary greatly, depending on the electrical energy source. In the present research problems connected with immediate initiation of the electric cars are not analysed.
Bibliografija: 24 jed.
Abstract.
Keywords: Električna vozila -- Električna mobilnost -- Emisije plinova; Slovenija